2001
DOI: 10.1016/s0142-694x(00)00026-0
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the conceptual design activity of interdisciplinary teams

Abstract: Citation: AUSTIN, S.A. ... et al, 2001. Mapping the conceptual design activity of interdisciplinary teams. Design Studies, 22 (3) SynopsisThe conceptual design phase of any project is, by its very nature, a vibrant, creative and dynamic period. It can also be disorganised with much backtracking accompanying the exchange of information between design team members. The transfer of information, ideas and opinion is critical to the development of concepts and as such, rather than being recognised as merely a comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 6 publications
1
45
0
Order By: Relevance
“…These results can be interpreted positively in the light of the current literature about the challenges in the early stages of product development [4] [39]. Investing more time in analyzing the design problem and the related value reports would help to reduce the knowledge gap related to the "design process paradox" [39], which is the lack of information in early phases when the major part of the final product value is committed.…”
Section: Verification Of the Approachmentioning
confidence: 85%
See 1 more Smart Citation
“…These results can be interpreted positively in the light of the current literature about the challenges in the early stages of product development [4] [39]. Investing more time in analyzing the design problem and the related value reports would help to reduce the knowledge gap related to the "design process paradox" [39], which is the lack of information in early phases when the major part of the final product value is committed.…”
Section: Verification Of the Approachmentioning
confidence: 85%
“…Investing more time in analyzing the design problem and the related value reports would help to reduce the knowledge gap related to the "design process paradox" [39], which is the lack of information in early phases when the major part of the final product value is committed. Moreover teams able to spend more time to embed multidisciplinary aspects in their analysis, have been proven to be more successful in delivering a highly valuable solution [4]. In the individual questionnaire participants have expressed a preference toward color-coded 3D models to enhance the individual perception of the value assessment results.…”
Section: Verification Of the Approachmentioning
confidence: 99%
“…Parks (2001) Process approach (generative, variant) Austin et al (2001), Goel et al (1997), Cherng et al (1998) (2001), Ullman (2003) Similarly, the degree of structure in methodology and team organisation may impact the team's performance. Furthermore, it is suggested that more structure may be required for distributed teams to be productive because of the physical barriers they face (Lurey and Raisinghani 2001).…”
Section: Design Approach Referencesmentioning
confidence: 99%
“…designers need to be able to work effectively in teams (Austin et al 2001, Denton 1997b, Busseri and Palmer 2000 b. modelling is a key concept in design; it takes many forms but simple pencil and paper sketches are possibly one of the most useful (Garner 2001, Cross 1999 c. meeting deadlines is an important skill for the professional and the individual or team must learn to plan to use their time effectively (Garner and Duckworth 2000) d. designers need to be able to communicate, indeed "sell" their ideas to clients e. even the most basic design context offers opportunities for ingenuity (Baker et al 2000) f. the direct handling of materials provides learning opportunities g. students must discuss the nature of `good design` h. designing should stretch intellectually, but can be fun (Baker et al 2000).…”
Section: The Key Messagesmentioning
confidence: 99%